2014
DOI: 10.1016/j.ijgo.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution anoscopy in women with cervical neoplasia

Abstract: HRA findings can be systematized, reducing the subjectivity of interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…68 Anal Pap smear and HRA have a wide-ranging sensitivity and specificity. 69,70 In one study of 300 HIV-positive men with positive anal Pap smears, only 54% demonstrated highgrade precursor lesions. 71 There is much debate regarding where this technique should be used and where it should fall in the colorectal surgeon's armamentarium.…”
Section: High-resolution Anoscopymentioning
confidence: 99%
“…68 Anal Pap smear and HRA have a wide-ranging sensitivity and specificity. 69,70 In one study of 300 HIV-positive men with positive anal Pap smears, only 54% demonstrated highgrade precursor lesions. 71 There is much debate regarding where this technique should be used and where it should fall in the colorectal surgeon's armamentarium.…”
Section: High-resolution Anoscopymentioning
confidence: 99%
“…Autores sugerem que a AAR pode ser um método superior à citologia para o rastreio do câncer anal 30 . Contudo, esse posicionamento ainda é controverso quando consideramos que a biópsia do canal anal, etapa constituinte do procedimento da anuscopia, apresenta algumas dificuldades, com relação tanto à execução quanto à interpretação dos achados histopatológicos 19 . Quando os exames da tríade clássica concordam entre si, há maior segurança diagnóstica.…”
Section: Discussionunclassified
“…As imagens colposcópicas foram analisadas após aplicação de ácido acético a 5% e solução de lugol a 2%. Na presença de áreas anormais sugestivas de NIA, foi efetuada biópsia, mesmo sem o resultado do exame citopatológico 19 .…”
Section: Métodosunclassified
See 1 more Smart Citation
“…9,10 Consequently, screening for precursor lesions has been encouraged in these groups. [11][12][13] Nevertheless, there is a need for further investigation into the profile of the women affected by this disease, since few studies have been conducted in this population.…”
Section: Introductionmentioning
confidence: 99%